Prescribing preoperative weight loss prior to major non-bariatric surgery for patients with elevated weight: a national provider survey (PREPARE provider survey) - McKechnie, Tyler; Thabane, Alex; Staibano, Phillip; Saddik, Maisa; Kuszaj, Olivia; Guez, Manon; Hong, Dennis; Doumouras, Aristithes; Eskicioglu, Cagla; Parpia, Sameer; Bhandari, Mohit (Frontiers in Surgery, 2025)
BackgroundThe surgical patient with obesity presents several challenges in intraoperative and postoperative care. We designed this cross-sectional survey to assess surgeon willingness to prescribe preoperative very low energy diets (VLEDs) and practice patterns in prescribing preoperative weight loss interventions for patients with obesity undergoing non-bariatric abdominal surgery.Methods and findingsWe conducted a cross-sectional survey of practicing surgeons in Canada who perform major non-bariatric abdominal surgery, reported in accordance with the Consensus-Based Checklist for Reporting of Survey Studies and utilizing non-probability convenience sampling. The primary outcome was willingness to prescribe preoperative VLED to obese patients undergoing major non-bariatric abdominal surgery for both benign and malignant indications. We created a multivariable proportional odds model to identify factors associated with willingness to prescribe VLEDs. A total of 78 participants completed and returned the survey (response rate 10.9%; mean age 43.54 ± 8.13 years; 48.72% female). Most surgeons (79.5%) felt that obesity significantly impacted the technical difficulty of their operations. We identified a disconnect between those surgeons who were willing prescribe VLEDs vs. those who actually prescribed them (78.2% vs. 30.8%, respectively). Approximately half of the surgeons reported being unfamiliar with VLEDs. Regression analysis identified practicing in academic institutions was associated with increased willingness to prescribe [odds ratio (OR) 3.71, 95% confidence intervals (CI) 1.01–13.7, p < 0.01].ConclusionAlthough the majority of surgeons feel that obesity adversely impacts perioperative care, only one-third routinely discuss preoperative VLEDs with their patients. Opportunities to increase awareness and evaluate the impact of VLEDs on patient outcomes remain high.